Cost and Accounting Concepts in Accounting and Their Accounting - Chilmatova Dilnoza Abdurahimovna; Mannopova Muazzamkhon Sultanbekovna (Global Scientific Publishing, 2022)
Cost, cost, cost and cost planning, cost control plays an important role in making management decisions in enterprises. This article explains the content and description of the concepts of costs, production costs and production costs. Definitions of direct and indirect production costs, as well as a costing system are given
Keywords: planning; costs; direct and indirect production costs